2022
DOI: 10.23910/1.2022.2758
|View full text |Cite
|
Sign up to set email alerts
|

Role of Brassinolide in Fruit Growth, Development, Quality and Cracking of Litchi Cv. Bombai Grown in New Alluvial Zone of West Bengal

Abstract: Bombai’ is a popular litchi variety of West Bengal but susceptible to fruit cracking which reduces the market price. Till now numbers of research trial conducted in litchi with different chemicals but reports on impact of application of brassinolide in reduction of fruit cracking maintaining quality attributes are limited. Therefore, an experiment was conducted during January-May of 2019–20 at the Experimental Farm of Horticultural Research station, Mondouri, Bidhan Chandra Krishi Viswavidayala, Nadia, West B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…Its physiological efficacy is activating the translocation and assimilation of metabolic materials, enhancing photosynthesis activity, and hormonal regulation of plant morphogenesis according to Guo et al (2011) andNisler (2018). These findings of brassinolide treatments agreed with those obtained by (Tadaion et al, 2014) on 'Khalili' grapevine; Roghabadi and Pakkish (2014) on 'Tak Danehe Mashhad' sweet cherry, they all found that brassinolide treatments significantly increased total soluble solids, total sugars, anthocyanin and vitamin C. Thapliyal et al (2016) on pear and Ghosh et al (2022). The application of BR can lead to an increase in sugars in fruits, as BR indirectly increases the content of abscisic acid (ABA), which in turn induces the sugar metabolic pathway.…”
Section: Total Sugars (%)supporting
confidence: 84%
“…Its physiological efficacy is activating the translocation and assimilation of metabolic materials, enhancing photosynthesis activity, and hormonal regulation of plant morphogenesis according to Guo et al (2011) andNisler (2018). These findings of brassinolide treatments agreed with those obtained by (Tadaion et al, 2014) on 'Khalili' grapevine; Roghabadi and Pakkish (2014) on 'Tak Danehe Mashhad' sweet cherry, they all found that brassinolide treatments significantly increased total soluble solids, total sugars, anthocyanin and vitamin C. Thapliyal et al (2016) on pear and Ghosh et al (2022). The application of BR can lead to an increase in sugars in fruits, as BR indirectly increases the content of abscisic acid (ABA), which in turn induces the sugar metabolic pathway.…”
Section: Total Sugars (%)supporting
confidence: 84%